VALIDITAS PENGEMBANGAN MODUL GEOMETRI BERBASIS BUDAYA DAERAH PESISIR SELATAN SUMATERA BARAT (Universitas PGRI Sumatera Barat, 2018)
Basically the school is a place of culture because the learning process is a civilizing process that is for students' academic achievement, to cultivate attitudes, knowledge, skills and traditions that exist in a cultural community. But in reality, the development of technology makes the loss of culture in students. For this reason, it is necessary to link learning with the culture of the area where students live. One of them is by making regional culture-based geometry modules. The purpose of this study was to look at the validity of the development of culture-based geometry modules in the South Coast region of West Sumatra. The instrument in this study is a validation sheet given to mathematicians and media experts. Based on the results of the three validators, the results of the validity of the culture-based Geometry module in the coastal areas south of West Sumatra that have been developed have yielded 89.3% with valid criteria.Keywords: Validity, Geometry Module, Regional Culture